2018
DOI: 10.1097/meg.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization for hepatocellular carcinoma: development and external validation of the Munich-TACE score

Abstract: We identified independent risk factors for patients treated with TACE. The newly constructed M-TACE score is superior to established staging systems and might prove helpful to identify patients who are most suitable for TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…When considering TACE as a treatment option, scoring systems could be of help in the decision-making process [54,55,56]. Although these scoring systems may not be validated for similar treatment strategies, the best fit patients for trans-arterial radio- or chemoembolization are the ones with preserved liver function as well [47].…”
Section: Overview On the Current State Of Liver Directed Therapy Smentioning
confidence: 99%
“…When considering TACE as a treatment option, scoring systems could be of help in the decision-making process [54,55,56]. Although these scoring systems may not be validated for similar treatment strategies, the best fit patients for trans-arterial radio- or chemoembolization are the ones with preserved liver function as well [47].…”
Section: Overview On the Current State Of Liver Directed Therapy Smentioning
confidence: 99%
“…In particular, the BCLC staging system represents the most commonly used score in Western countries to predict prognosis and guide treatments. However, two different studies showed that the prognostic value of BCLC was limited in the setting of TACE [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a multitude of TACE-specific staging systems have been developed, such as the hepatoma arterial embolization prognostic (HAP) score [ 26 ], the selection for transarterial chemoembolization treatment (STATE) score [ 27 ], the Munich-transarterial chemoembolization score (M-TACE) [ 25 ], the six-and-twelve score [ 28 ], and the albumin–bilirubin (ALBI) grade [ 29 ]. These prognostic scores are based on prediction factors collected before the cTACE procedure, such as tumor characteristics (e.g., tumor size, vascular invasion), hepatic function (e.g., albumin, bilirubin blood levels), blood markers such as alpha-fetoprotein (AFP), and chronic liver severity indexes such as the Child–Pugh score [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three unidimensional classifications were tested: TNM [25], Child-Pugh score [26], and ALBI-grade [27]. Additionally, a recently published TACE-specific score (M-TACE) [28] was applied.…”
Section: Tested Staging Systemsmentioning
confidence: 99%